Serum Infliximab, Antidrug Antibodies, and Tumor Necrosis Factor Predict Sustained Response in Pediatric Crohn's Disease. Issue 6 (June 2016) - Stein, Ronen; Lee, Dale; Leonard, Mary B.; Thayu, Meena; Denson, Lee A.; Chuang, Emil; Herskovitz, Rita; Kerbowski, Theresa; Baldassano, Robert N.
Abstract : Background: Serum infliximab (s-IFX) levels, antibodies to IFX (ATI), and inflammatory markers are important in predicting clinical outcomes in adults, but their roles in pediatric Crohn's disease (CD) require further study. The primary aim of this study was to determine the association between serologic parameters during induction and ongoing IFX therapy at 12 months in pediatric CD. Methods: S-IFX, ATI, serum tumor necrosis factor alpha (s-TNF-α), and C-reactive protein were measured at IFX initiation, 10 weeks, 6 months, and 12 months in a prospective cohort study of children with CD at a single tertiary care center. Results: At 12 months, 60 of 77 participants (78%) remained on IFX. Participants who completed 12 months of IFX had higher 10-week median s-IFX levels (20.40 μg/mL; interquartile range [IQR], 11.20–35.00] versus 8.70 μg/mL; IQR 0.90–16.90; P = 0.01), a greater proportion with undetectable 10-week ATI ( P = 0.008), and a greater median change in s-TNF-α between baseline and week 10 (−5.96 pg/mL; IQR, −8.73 to −4.17 versus −1.76 pg/mL; IQR, −5.60 to 0.30; P = 0.006). Receiver operating characteristic analysis to predict ongoing IFX at 12 months showed area under the curve (95% confidence interval) for 10-week s-IFX and change in s-TNF-α from baseline to 10 weeks to be 0.71 (0.54–0.88) and 0.74 (0.58–0.91), respectively. C-reactive protein was not associated with ongoing therapy. Conclusions: ATI, s-IFX, and s-TNF-α during IFX induction are associated with 12-month clinical outcomes in pediatric CD. Future studies are needed to further define the clinical role of s-TNF-α measurement and to compare the clinical utility of 10 and 14-week ATI and s-IFX levels. Abstract : Supplemental Digital Content is Available in the Text.Article first published online 8 April 2016.